Making use of water droplets as a sustainable green energy source. Issue 1 (27th July 2022) - Yang, Yanqin; Lee, Chengkuo
Abstract : Historical milestones of the development of triboelectric nanogenerators (TENGs) and liquid–solid‐based electricity generator.